Study of prevalence of secondary hyperparathyroidism in chronic renal failure in hadoti region - Dayma, Chiranjee Lal; Ajmera, Devendra; Jelia, Shiv Charan; Jain, Pankaj (International Journal of Research in Medical Sciences, 2019)
Background: Secondary hyperparathyroidism is known and early complication of chronic renal failure patients. Aim of this study was to assess the prevalence of secondary hyperparathyroidism and correlation between serum parathyroid hormone level with biochemical parameters in renal failure patients in tertiary care hospital in Kota, Rajasthan. Methods: A cross sectional observational study was carried out in 50 patients who had creatinine clearance of 30ml/min/1.73m2 or less for greater than 6 weeks attended the OPD of department of General Medicine, New Medical College hospital, Kota, Rajasthan from May 2018 to November 2018. Investigations like complete blood count, renal function test, urine routine microscopy and USG abdomen with serum parathyroid hormone, serum phosphorus, serum calcium levels were done. Serum parathyroid hormone level was done by calorimetric method. Results: The prevalence of secondary hyperparathyroidism in our study was 72%. In hyperparathyroidism patient’s serum calcium level was low and the difference was highly significant (p<0.001). There is negative correlation between S.PTH and S. calcium level (r=-0.536). Mean serum calcium level in our study is 1.6mmol/l. In hyperparathyroidism patient’s serum phosphate level was high and the difference was highly significant (p<0.001). There was positive correlation between S.PTH and S.PO4 level (r=0.402). Mean serum phosphorus level in our study is 5.7 mg/dl. Prevalence of hyperparathyroidism was high among CRF patients with normal BP than hypertensive patients and with normal sugar than diabetics but the difference in proportion was not significant (p=0.87, p=0.98 respectively). 90% patients were on haemodialysis while 10% patients were on conservative management. Conclusions: Early detection of secondary hyperparathyroidism in chronic renal failure patients can reduce its complications like bone fracture and cardiovascular complications.